Fracture mechanics, enamel thickness and the evolution of molar form in hominins. (22nd January 2020) - Schwartz, Gary T.; McGrosky, Amanda; Strait, David S.
Abstract : As the tissue most directly responsible for breaking down food in the oral cavity, the form and function of enamel is obviously of evolutionary significance in humans, non-human primates and other vertebrates. Accordingly, a standard metric, relative enamel thickness (RET), has been used for many decades to provide insights into vertebrate and human palaeobiology. Relatively thick enamel has evolved many times in vertebrates including hominoids (the group to which living humans and fossil hominins belong), and this pattern is thought to provide information about taxonomy, phylogeny, functional anatomy and diet. In particular, relatively thick enamel is thought to make tooth crowns strong so that they resist fractures associated with eating mechanically resistant foods. Here, we use current models of tooth biomechanics to show that RET is at best only moderately informative of function and diet in living hominoids and fossil hominins, and at worst provides misleading information. We propose a new metric, absolute crown strength, to assess the resistance of teeth to fracture, and identify what may be a novel characteristic of tooth strength in fossil hominins.